Integrating the full range of security cooperation programs into Air Force planning : a analytic primer - Moroney, Jennifer D. P., 1973-; Hogler, Joe L.; Kennedy-Boudali, Lianne; Pezard, Stephanie; Project Air Force (U.S.). Strategy and Doctrine Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 2011)
The Air Force and other Department of Defense entities conduct a host of security cooperation activities with partner air forces. Many programs are available for use when working with partner countries in a variety of contexts. However, there is currently no process for systematically tracking all these programs and activities. This report supplies Air Force planners with more-accessible information about resources for security cooperation, the rules that govern their use, and their application methods. It does so via an analytical construct created to illustrate how these resources can be employed in partner countries with varying degrees of capability, capacity, and willingness to work with the United States. The authors present an illustrative vignette to demonstrate how this construct may be used in a situation that requires a security cooperation plan. A set of program pages is also included to help security cooperation planners determine the key components of a security cooperation plan: the partner countries to be addressed by the plan, the programs to be used, the types of activities to be conducted through those programs, and program funding information.
"RAND Project Air Force."
Includes bibliographical references (p. 165-167).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Planning -- Evaluation; Military planning -- United States -- Evaluation; Military policy -- International cooperation; United States -- Military relations -- Foreign countries